From inconsistency to sustainability: ICU night huddle compliance improvement through a structured QI approach - Prasobh PV Mukundan; Alisha Karki (Future Healthcare Journal)
Introduction: Effective communication and structured handovers are critical for patient safety and team coordination in intensive care units (ICUs). Night shift handovers often occur separately for doctors and nurses, leading to inconsistent communication, unclear role delineation and missed safety-critical tasks. To address this, a structured ICU Night Huddle was introduced as a quality improvement (QI) initiative to enhance team coordination and compliance. Materials and methods: This QI project followed a plan–do–study–act (PDSA) cycle over two phases: (1) initial QIP (September 2023–March 2024): a structured Night Shift Briefing Checklist was implemented to ensure standardised communication and that compliance was monitored; (2) re-audit (September 2024–December 2024): targeted interventions were implemented to address compliance gaps:• Phase 1: Checklist placed in Doctors’ Hub (22 September 2024)• Phase 2: WhatsApp group reminders to doctors (1 October 2024)• Phase 3: Message of the Week in Morning Huddle (14 October 2024)• Phase 4: Nursing In-Charge Involvement (15 November 2024)Weekly compliance rates were recorded and analysed pre- and post-interventions. Results and discussion: Compliance improved from 32.8% (initial QIP) to 70.7% (re-audit), a 37.9% increase (Fig 1).The impact of each intervention was assessed as follows: • Phase 1: Checklist in Doctors’ Hub (22 September 2024): initial compliance was low, with inconsistent adherence. • Phase 2: WhatsApp reminders (1 October 2024): compliance increased to ∼57%, but some nights were still missed due to lack of structured accountability. • Phase 3: Message of the Week in Morning Huddle (14 October 2024): reinforcement through daily reminders resulted in a boosted compliance of ∼71%. • Phase 4: Nursing In-Charge Involvement (15 November 2024): sustained compliance of ∼75% was achieved by actively engaging nursing staff, ensuring a shared responsibility rather than relying solely on doctors.Challenges: night huddle non-compliance persisted due to: • Workload pressure – If ICU was busy, staff may have skipped the huddle; • Forgetting/skipping: some days were missed even with reminder; • No direct accountability: night huddle often relied on motivated individuals; • Staff rotation issues: new staff may not have been fully aware of the expectation; • Nursing–doctor coordination issues: some shifts lacked direct interaction.What can be done to sustain and improve compliance? • Make the huddle a ‘mandatory’ checklist item: embed it in ICU workflow; • Assign a ‘Night Huddle Lead’ per shift: doctor/nurse takes responsibility; • Periodic reintroduction of Message of the Week: to reinforce habit; • Discuss non-compliance in the morning handover: create accountability; • Recognition for consistent compliance: reward teams maintaining 100% adherence; • Future re-audit in 6 months: evaluate sustainability and impact of interventions. Conclusions: • Re-audit demonstrated a substantial improvement in compliance; • Structured reminders and leadership involvement significantly increased adherence; • Sustained improvement requires formal integration into ICU workflow; • Plan for a future re-audit in 6 months to ensure long-term adherence.This project highlights the importance of multidisciplinary ownership in quality improvement and provides a scalable model for other ICUs aiming to enhance handover effectiveness.